A Note on Orthogonal Fuzzy Metric Space, Its Properties, and Fixed Point Theorems. (11th May 2022) - Javed, Khalil; Asif, Awais; Savas, Ekrem
Abstract : The article generalizes the notion of orthogonal fuzzy metric space into a broader term, named as orthogonal picture fuzzy metric space. The obtained results improve and extend the idea of the orthogonal fuzzy metric space and its related results. However, this article outstretches the above-mentioned notion further into a newly defined concept, named as orthogonal picture fuzzy metric space. A detailed insight is given into the topic by presenting some fixed point results in the frame of the newly defined structure. To elaborate the results more precisely, some concrete examples are given.